Randomized Trial of a Tailored Cognitive‐Behavioral Therapy Mobile Application for Anxiety in Patients with Incurable Cancer. (25th January 2019) - Greer, Joseph A.; Jacobs, Jamie; Pensak, Nicole; MacDonald, James J.; Fuh, Charn‐Xin; Perez, Giselle K.; Ward, Alina; Tallen, Colleen; Muzikansky, Alona; Traeger, Lara; Penedo, Frank J.; El‐Jawahri, Areej; et al.
Abstract: Background: The aim of this study was to test the efficacy of a tailored cognitive‐behavioral therapy (CBT) mobile application (app) to treat anxiety in patients with incurable cancer. Materials and Methods: Patients with incurable cancers ( n = 145) who reported elevated anxiety symptoms at two cancer centers were randomized to receive either the CBT mobile app for anxiety or a mobile health education program (control) delivered via tablet computers, which patients self‐administered over 12 weeks. To assess anxiety, depression symptoms, and quality of life (QOL), we used the Hamilton Anxiety Rating Scale (HAM‐A, primary outcome), Clinical Global Impression Scale, Hospital Anxiety and Depression Scale (HADS), Patient Health Questionnaire‐9, and Functional Assessment of Cancer Therapy‐General at baseline and 12 weeks. Analysis of covariance models were calculated to assess intervention effects on patient outcomes. Results: Patients (73.8% female; 91.0% white; mean age = 56.45 years, SD = 11.30) in both study groups reported improvements in anxiety, depression symptoms, and QOL from baseline to postassessment, with no significant differences in any outcome measure between groups. Secondary analyses showed that, among the subgroup of patients with severe baseline anxiety, those randomized to the CBT app had greater improvements on the HAM‐A (Mean Difference = 7.44, standard error [SE] = 3.35, p = .037) and HADS‐Anxiety Subscale (Mean Difference = 4.44, SE = 1.60, p = .010) compared with the control group. Conclusion: Both the tailored CBT app for anxiety and the health education program were associated with improvements in anxiety, mood, and QOL, but these outcomes did not differ between study groups. The CBT app was more beneficial than health education for patients with severe baseline anxiety. Abstract : Many patients with advanced cancer report clinically significant anxiety symptoms. Cognitive behavioral therapy (CBT) is a treatment for anxiety that has been shown to be successful. This study tested the efficacy of a CBT intervention that was adapted to a mobile application that could be self‐administered, comparing its use to the use of a health education program administered similarly.